AESTHETIC SPACE IN SYNTHETIC CUBISM, INTERPRETATION ANALYSIS OF ARMEN NAZARUDDIN'S PAINTINGS - Mukhsin Patriansah; Ria Sapitri; Husni Mubarat (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2022)
This study aims to see the aesthetic spaces in synthetic cubism by Armen Nazaruddin. When mastering the techniques, tools and materials that are mastered, the next problem that arises is the application of aesthetic values in the form of works of art. Therefore, describing an experience of having a sense and being intellectual in giving birth to his work of art. This is what the author did to conduct an object study of Armen Nazaruddin's painting, which later could be used as a reference and reference in the development of painting in Indonesia, especially in West Sumatra. This painting really considers the principles of making principles in detail and meticulously as well as the stars of the message and meaning in it. Artists experiment with how to make use of objects around them that have no value to become more appropriate in accordance with the Minang Kabau philosophy, namely, "Nature Takambang Becomes a Teacher". Keywords: Aesthetics, Painting, Synthetic Cubism, ExperimentRuang Estetika Dalam Kubisme Sintetik, Analisis Interpretasi Terhadap Lukisan Armen NazaruddinAbstrakPenelitian ini bertujuan untuk melihat ruang-ruang estetis dalam kubisme sintetik karya Armen Nazaruddin. Ketika penguasaan teknik, alat dan bahan sudah dikuasai, persoalan selanjutnya yang muncul adalah terapan nilai estetika dalam wujud karya seni. Oleh karena itu, seniman dituntut memiliki suatu kepekaan rasa dan intelektual dalam melahirkan karya seninya. Hal inilah yang mendasari penulis melakukan objek kajian terhadap karya seni lukis Armen Nazaruddin, yang nantinya bisa dijadikan acuan serta referensi dalam perkembangan seni lukis di Indonesia, khususnya di Sumatera Barat. Lukisan ini sangat mempertimbangkan prinsip-prinsip penyusunan secara detail dan teliti dan juga tersirat pesan dan makna di dalamnya. Seniman senantiasa bereksperimentasi dengan cara memanfaatkan benda-benda yang ada di sekitarnya yang tidak memiliki nilai menjadi lebih bernilai sesuai dengan falsafah minang kabau yakni “alam takambang jadi guru”. Kata kunci :  Estetika, Seni Lukis, Kubisme Sintetik, Eksperimentasi